Психологічне підґрунтя мовної передачі емоції дистресу - Вербицька, Анна Едурдівна; Verbytska, A. Е. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті досліджуються складники психологічного підґрунтя мовної передачі емоції дистресу, а саме горя та страждання. Здійснено огляд британської преси 2011–2014 рр. та виокремлено фрустраційні ситуації, які ініціюють виникнення горя-страждання. Проаналізовано основний психологічний фактор внутрішнього переживання емоції дистресу – втрату. Зосереджено увагу на лексичних засобах мовної передачі емоції дистресу. У результаті аналізу статей виокремлено п’ять видів дистресу, що доводить глобальність впливу емоції на різні сфери життя людини. The article examines the components of the psychological grounds of distress verbal expression, namely, grief and suffering. Having carried out a review of the British press of 2011–2014 the frustrative situations were singled out triggering the emergence of grief-suffering: violence, the absence of vital things, the situations that unbalance. Loss as the basic psychological factor of inner experience of the distress is analyzed. The results of the research demonstrate the primary status of frustrative situations in the system of emergence of the distress which occurs due to the loss. Attention is focused on the lexical means of the verbal expression of distress. Prevailing amount of lexical means refers to an explicit verbal expression. Due to the analysis of the articles the five types of distress are identified: emotional, physical, psychological, mental, and sustained/prolonged. The numerous kinds of the distress prove the global impact of this emotion on a person’s life.
Psychological Grounds for the Distress Verbal Expression
Keywords: базова емоція; basic emotion; дистрес; distress; горе; grief